Mobilização rápida de citocromo-oxidase por estimulação sensorial em córtex visual de gatos e primatas - Ribeiro, Sidarta Tollendal Gomes (1994)
The cytochrome oxidase fast mobilization was studied in twelve cats (Felis catus) and three monkeys (Cebus apella). Visual stimulus of low spatial frequency, with variations in colour and brightness and no spatial orientation allowed the observation of cytochrome oxidase-rich patches in flattened sections of cat's visual cortex. The patches appeared in Vl, V2 and V3 supragranular layers, as well as in other extra-striated areas. Morphologically, those patches are equivalent to the blobs recently described in cat by improved histochemical methods. The morphometric analysis reveals that blobs medium size tend to increase from Vl to V2 and from V2 to V3. The densitometric analysis of monocularly stimulated monkey' s striate cortex sections shows a cytochrome-oxidase activation peak after thirty minutes of stimulation, followed by a decrease in optical density at greater times. This indicates that the phenomena is composed of two distinct phases. The monocular stimulation by stroboscopic light shows ocular dominance columns in monkey's Vl after thirty minutes. The cytochrome oxidase fast mobilization phenomena may be the product of the immediate activation of one or more genes of the enzyme' s subunits, of allosteric interactions with ATP, or of local redistribution of mitochondria.